Persepsi Merek Sebagai Mediator Dalam Pengaruh Strategi Pemasaran Terhadap Keputusan Pembelian Mahasiswa - Sahabuddin, Romansyah; Farid, Andi Muhammad; Fariski, Muh; Rahman, Fatur; Arif, Hery Maulana (Abadi Institute, 2024)
This research aims to investigate the effect of marketing strategies on purchasing decisions among Management students at the Faculty of Economics and Business, Makassar State University (FEB UNM), with a focus on brand perception as an intervening variable. The study employed a survey method using purposive sampling, involving 310 active students as respondents. Data were gathered via questionnaires and analyzed using path analysis. The findings indicated that marketing strategies significantly affect students' purchasing decisions, both directly and through brand perception. These results offer valuable insights for marketers in the education sector to place greater emphasis on brand perception to enhance the effectiveness of their marketing strategies.